If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + 9(8 + 5c) = 0 10 + (8 * 9 + 5c * 9) = 0 10 + (72 + 45c) = 0 Combine like terms: 10 + 72 = 82 82 + 45c = 0 Solving 82 + 45c = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-82' to each side of the equation. 82 + -82 + 45c = 0 + -82 Combine like terms: 82 + -82 = 0 0 + 45c = 0 + -82 45c = 0 + -82 Combine like terms: 0 + -82 = -82 45c = -82 Divide each side by '45'. c = -1.822222222 Simplifying c = -1.822222222
| f(x)=3x^2-2x+6 | | x+28=25 | | 56v^2+17vb-3b^2= | | 8+2x-4=6+4(x-1) | | 8+2x-4=6+4 | | -5(-9+-10t)+10(3+-5t)= | | 3[x+2(x-7)]=-60 | | 5x+28=35 | | 6-(-5)r=5r-3 | | -9(-1+-4k)+k= | | 2(x+4)=6-1(3x-2)-1 | | Y=log[4](x^2-4x-21) | | x-7=-.25 | | 8x-29=-77+2x | | 7x-28=17+2x | | 2(6x+6)+8=8x+18 | | 3(2a-2)=2(3a-3) | | 5(3+6x)-4=41 | | 6x^2+33x+42=0 | | x^2-2x+56=0 | | x^2-2x+56=0 | | 6+6(-3-6z)= | | 8(6x-8)-8(2+3x)=-32 | | 5(10+6m)= | | -(6+4x)-8(8x-3)=-50 | | -7+5(2r-6)=-107 | | 5(3x+9)(5x-15)=0 | | (x-4)(x+1)=14 | | e^9x=3 | | 5(1+3b)+7(7-3b)=30 | | -5p+-4(-p+4)= | | 8-11=-13 |